2019
DOI: 10.1088/1757-899x/527/1/012004
|View full text |Cite
|
Sign up to set email alerts
|

Slope stability analysis using modified Fellenius’s and Bishop’s method

Abstract: Analysis of slope stability is very important as many structures in hilly areas failed due to instability of slope. The aim of this study is to determine the factor of safety (FOS) of slopes located at Pahang Matriculation College by using limit equilibrium method. Two methods known as modified Fellenius’s method and modified Bishop’s method are used in this study. Laboratory testing involving index and engineering properties are conducted to determine the properties of soil within the study area. The soil at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 11 publications
1
11
0
1
Order By: Relevance
“…The soil worked by Fortes [14] is the closest geologically with Point 1, since they are both tropical soils. Probably, the difference between the tests by Mello (1946) and Schroder [15] is due to the geological formation of the studied soil, since the last two are temperate soils [16][17][18][19][20][21][22][23][24][25].…”
Section: Comparison Of Resultsmentioning
confidence: 99%
“…The soil worked by Fortes [14] is the closest geologically with Point 1, since they are both tropical soils. Probably, the difference between the tests by Mello (1946) and Schroder [15] is due to the geological formation of the studied soil, since the last two are temperate soils [16][17][18][19][20][21][22][23][24][25].…”
Section: Comparison Of Resultsmentioning
confidence: 99%
“…A convergence tolerance and iteration ceiling limit of 0.0001 and 500, respectively, are considered for the elasto-plastic analysis process (Smith & Griffiths, 2004). In numerical analysis of slope stability, the FoS is usually reported up to 2 decimal places depending on the type of numerical technique employed (Zolkepli et al, 2019). However, for mining applications such as that considered in this study, FoS values reported up to 1 decimal place is deemed sufficient.…”
Section: Shear Strength Reduction Techniquementioning
confidence: 99%
“…the ground surface does not always form flat plane or have differences elevation between one place and another other to form a slope (slopes) [5]. Landslide is a disaster nature that often occurs on the slopes natural or artificial [6] [7]. The slope is a ground surface inclined and forms a certain angle to a horizontal plane [8].…”
Section: Introductionmentioning
confidence: 99%